EVALUASI PENGGUNAAN TERAPI OBAT KARDIOVASKULAR PADA PASIEN HIPERTENSI YANG DIRAWAT DI RSUP DR. M. DJAMIL PADANG - Marsellinda, Elsa; Aulia, Dhea Suci (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Hypertension is one of the major modifiable risk factors associated with cardiovascular disease, and its prevalence and severity increase with age. The purpose of this study was to look at the description of the use of hypertension drug therapy, gender and age level of patients treated at dr. M. Djamil Padang Hospital October-December 2023 period. Data were collected retrospectively from the medical records of hypertensive patients admitted to the internal medicine ward. period October to December 2023 analyzed descriptively. Based on the results of the study of 131 hypertensive patients who were treated at DR. M.Djamil Padang Hospital in the October-December 2023 period, it was concluded that male sex patients were more than female, based on the age of patients with an age range of 56 - 65 years and the use of the most widely used antihypertensive therapy was 3 combinations.